Bimanual Tangible Interaction with Mobile Phones - Edge, Darren; Blackwell, Alan (TEI 2009 Conference on Tangible and Embedded Interaction, 2009)
In the context of tangibility, mobile phones are rapidly becoming sensor-rich handheld computers with the potential to take better advantage of our physical capabilities and our lifetime of experiences interacting both in and with the world around us. In this paper, we analyse four different ways in which mobiles can be used to represent and control digital information, showing that each resulting interaction style is characterized by a unique coordination of the user’s attention and two hands in relation to the mobile device. We present our analysis in terms of a framework that can be used to critically examine future schemes of bimanual interaction with mobile phones.